Microsoft Visual C++/CLI step by step - Templeman, Julian (Microsoft Press, 2013)
Your hands-on guide to Visual C++/CLI fundamentals Expand your expertise--and teach yourself the fundamentals of the Microsoft Visual C++/CLI language. If you have previous programming experience but are new to Visual C++, this tutorial delivers the step-by-step guidance and coding exercises you need to master core topics and techniques. Discover how to: Write and debug object-oriented C++ programs in Visual Studio 2012 Utilize the various features of the C++/CLI language Make use of the Microsoft .NET Framework Class Library Create a simple Windows Store app Use .NET features such as properties, delegates and events Access data from disparate sources using ADO.NET Create and consume web services using Windows Communication Foundation Work effectively with legacy code and COM.
Online resource; title from title page (Safari, viewed September 5, 2013)
Keywords: Microsoft .NET Framework; C++/CLI (Computer program language); C++ (Computer program language); C++/CLI (Langage de programmation); C++ (Langage de programmation)